The mechanical properties of AA6082/AA1050 dissimilar joints subjected to multi-pass friction stir processing. (30th July 2021) - Muribwathoho, Oritonda; Msomi, Velaphi; Mabuwa, Sipokazi; Merdji, Ali
Abstract: This paper reports 'on the influence of multi-pass friction stir processing (MFSP) on AA6082/AA1050 dissimilar joints produced by friction stir welding (FSW) technique. The produced dissimilar joints were subjected to 1pass (1P), 2pass (2P), 3pass (3P), and 4pass (4P) friction stir processing (FSP) procedure. The microstructural analysis showed the decrease in grain size with an increase in number of FSP passes. However, the tensile properties showed inverse relations with the number of FSP passes and this was linked to the dissolution of strengthening precipitates. The fractographic analysis showed the presence of dimples on all the fractured surfaces and that is an indication ductile fracture. However, the fractured surface of the 4P specimen was characterized by the presence of dimples mixed with flat structures which indicates ductility mixed with brittleness. There was no major influence of the number' of FSP passes on the microhardness of the AA6082/AA1050 joint.